CREATE Activities for Early Career Researchers in 2026 - Theresa Frohn; Carolina C. Silva; Melanie Bamert; Jessica Schiller; Laura Gördes; Vivien Hajak; Ann-Kathrin Sowa (European Health Psychologist, 2026)
CREATE (Collaborative Research and Training in the EHPS) is an early career researcher (ECR) subdivision of the European Health Psychology Society (EHPS), dedicated to supporting the professional development, networking, and engagement of ECRs in health psychology. This report provides an overview of CREATE’s initiatives and activities for 2026, covering activities at the annual EHPS Conference in Pafos, Cyprus, as well as initiatives throughout the year. Key activities at the conference include the CREATE pre-conference workshop, which this year focuses on the use of artificial intelligence in research, the “Meet the Experts” sessions, and the Early Career Researcher Spotlight Talks. Throughout the year, CREATE offers a range of initiatives, including webinars, networking events, and writing retreats. In addition, the report highlights funding opportunities and outlines ways to stay informed about CREATE activities.